2003
DOI: 10.2172/918222
|View full text |Cite
|
Sign up to set email alerts
|

Ionization coefficient approach to modeling breakdown in nonuniform geometries.

Abstract: This report summarizes the work on breakdown modeling in nonuniform geometries by the ionization coefficient approach. Included are: 1) fits to primary and secondary ionization coefficients used in the modeling; 2) analytical test cases for sphere-to-sphere, wire-to-wire, corner, coaxial, and rod-to-plane geometries; a compilation of experimental data with source references; comparisons between code results, test case results, and experimental data. A simple criterion is proposed to differentiate between coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 18 publications
5
32
0
1
Order By: Relevance
“…Therefore, eff is a function of the local effective field and the function eff (E eff ) is deduced from an analytical fits to experimental data obtained in air by Warne et al 22 A plot of eff (E eff ) is shown in Figure 1. The other transport coefficients of Eq.…”
Section: A Physical Modelmentioning
confidence: 99%
“…Therefore, eff is a function of the local effective field and the function eff (E eff ) is deduced from an analytical fits to experimental data obtained in air by Warne et al 22 A plot of eff (E eff ) is shown in Figure 1. The other transport coefficients of Eq.…”
Section: A Physical Modelmentioning
confidence: 99%
“…Here we apply ionization coefficients to determine threshold breakdown voltage levels [21]. Figure 87 illustrates an electron avalanche and charge growth in an electric field.…”
Section: Threshold Levelsmentioning
confidence: 99%
“…In order to calculate the expected breakdown voltage between the pin electrode and the other two objects in the problem (the coupon and the cable) we follow the method outlined in [21]. The geometry is gridded as shown in Figure 90, using elements that have edge lengths of approximately 1 mm.…”
Section: Calculationmentioning
confidence: 99%
“…In the fluid model, the ionization and attachment frequencies are usually combined as the effective ionization frequency ν eff , which can be expressed in terms of the electron drift velocity v d = μ e E (m/s) as [52], [53] …”
Section: ) Plasma Diffusionmentioning
confidence: 99%